Application of piconewton forces to individual filopodia reveals mechanosensory role of L-type Ca2+ channels. (May 2022) - Efremov, Artem K.; Yao, Mingxi; Sun, Yuze; Tee, Yee Han; Sheetz, Michael P.; Bershadsky, Alexander D.; Martinac, Boris; Yan, Jie
Abstract: Filopodia are ubiquitous membrane projections that play crucial role in guiding cell migration on rigid substrates and through extracellular matrix by utilizing yet unknown mechanosensing molecular pathways. As recent studies show that Ca 2+ channels localized to filopodia play an important role in regulation of their formation and since some Ca 2+ channels are known to be mechanosensitive, force-dependent activity of filopodial Ca 2+ channels might be linked to filopodia's mechanosensing function. We tested this hypothesis by monitoring changes in the intra-filopodial Ca 2+ level in response to application of stretching force to individual filopodia of several cell types using optical tweezers. Results show that stretching forces of tens of pN strongly promote Ca 2+ influx into filopodia, causing persistent Ca 2+ oscillations that last for minutes even after the force is released. Several known mechanosensitive Ca 2+ channels, such as Piezo 1, Piezo 2 and TRPV4, were found to be dispensable for the observed force-dependent Ca 2+ influx, while L-type Ca 2+ channels appear to be a key player in the discovered phenomenon. As previous studies have shown that intra-filopodial transient Ca 2+ signals play an important role in guidance of cell migration, our results suggest that the force-dependent activation of L-type Ca 2+ channels may contribute to this process. Overall, our study reveals an intricate interplay between mechanical forces and Ca 2+ signaling in filopodia, providing novel mechanistic insights for the force-dependent filopodia functions in guidance of cell migration.